2010
DOI: 10.1002/ange.200906820
|View full text |Cite
|
Sign up to set email alerts
|

Hybridmaterialien aus Nucleinsäuren und organischen Polymeren: Synthese, Überstrukturen und Anwendungen

Abstract: Die Entwicklung von Hybridstrukturen aus Biomakromolekülen und organischen Polymeren, die über kovalente Bindungen miteinander verknüpft sind, ist ein intensiv bearbeitetes Gebiet. Während die Kombination von Proteinen/Peptiden mit synthetischen Makromolekülen bereits umfassend untersucht worden ist, sind bisher weit weniger Beispiele für Nucleinsäure‐Polymer‐Hybride bekannt. In diesem Aufsatz stellen wir ausgewählte Beispiele dieser interessanten Materialklasse vor, deren Vertreter lineare Blockcopolymere, Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 162 publications
0
12
0
1
Order By: Relevance
“…[17][18][19] Potent drugdelivery vehicles based on DNABCps have also been used with antiviral DNA and towards anticancer therapeutics. [7,8] This strategy, known as "blocking-to" (b-t), offers the advantage that the composition of the polymer segment is well known prior to conjugation to the DNA segment. [24] The primary method to obtain DNABCps involves separate syntheses of the polymer and the DNA segments, followed by a conjugation reaction to covalently attach them.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] Potent drugdelivery vehicles based on DNABCps have also been used with antiviral DNA and towards anticancer therapeutics. [7,8] This strategy, known as "blocking-to" (b-t), offers the advantage that the composition of the polymer segment is well known prior to conjugation to the DNA segment. [24] The primary method to obtain DNABCps involves separate syntheses of the polymer and the DNA segments, followed by a conjugation reaction to covalently attach them.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Among these, DNA block copolymers (DNABCps) are a novel class of bioconjugates that have a DNA segment covalently attached to an organic polymer segment. [7][8][9] By tuning the properties of the DNA and the organic polymer, the properties of the DNABCp can be tailored. Such control has led to DNABCps that form reversible micelles and nanoscale assemblies, including some that are responsive to DNA-based recognition events.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Die Strukturen solcher Systeme beruhen im Allgemeinen auf reversiblen Bindungen wie hydrophoben Wechselwirkungen, Wasserstoffbrückenbildung oder ionischen Interaktionen, die ein dynamisches Verhalten erlauben 2829 und in zunehmendem Maße auch Nukleinsäuren (Nukleinsäure‐Polymerhybride)30 immer mehr Anklang finden.…”
Section: Strukturaufbau Durch Selbstorganisationunclassified
“…The first DNA micelles, formed from DNA-poly(propylene oxide) hybrids, were introduced by Herrmann and co-workers. [16][17][18][19][20][21] Because of the recognition abilities of DNA, such micelles can easily be equipped with any desired functionalities. [16] In addition, it was demonstrated that the DNA strands are accessible to enzymes, and can undergo enzymatic conversions.…”
Section: Introductionmentioning
confidence: 99%